A new species of Simulium ( Simulium ) (Diptera: Simuliidae) from Genting Highlands, Malaysia - Ya'cob, Zubaidah; Takaoka, Hiroyuki; Low, Van Lun; Sofian-Azirun, Mohd (Elsevier, 2018)
Simulium (Simulium) rasuli sp. nov. is described from two females collected by a Malaise trap in Genting Highlands, Peninsular Malaysia. This new species is placed in the Simulium christophersi species-group of the subgenus Simulium. The female of this new specie is characterized by the scutum with three longitudinal vittae, dark legs, claw with a small subbasal tooth, and ovipositor valve triangular with its inner margin nearly straight. This new species is distinguished in the female from all the six named species of the species-group by the entirely brownish-black femora and tibiae.